Outcomes for older people with screening-detected versus existing chronic kidney disease: a cohort study with data linkage - Anna K Forbes; José M Ordóñez-Mena; Winnie Mei; Clare J Taylor; Nicholas Jones; Jennifer A Hirst; FD Richard Hobbs (BJGP Open)
Background: Chronic kidney disease (CKD) is a common health problem associated with increased risk of cardiovascular disease (CVD), end-stage kidney disease (ESKD), and premature death. It is estimated that one-third of people aged ≥70 years have CKD globally, many of whom are undiagnosed, but little is known about the value of screening. Aim: To compare the risk of adverse health outcomes between people with an existing diagnosis of CKD and those identified through screening, and identify factors associated with mortality in CKD. Design & setting: Prospective cohort study of 892 primary care patients aged ≥60 years with CKD (existing and screening detected) in Oxfordshire, with data linkage to civil death registry and secondary care. Method: Hazard ratios (HRs) and 95% confidence intervals (CIs) were estimated using Cox proportional hazard models to compare the risk of all-cause mortality, hospitalisation, CVD, ESKD separately, and as a composite between CKD groups, as well as to identify factors associated with mortality. Results: After a median follow-up of 3–5 years, 49 people died, 512 were hospitalised, 78 had an incident CVD event, and none had an ESKD event. There was no difference in the composite outcome between those with existing CKD and those identified through screening (HR 0.94, 95% CI = 0.67 to 1.33). Older age (HR 1.10, 95% CI = 1.06 to 1.15), male sex (HR 2.31, 95% CI = 1.26 to 4.24), and heart failure (HR 5.18, 95% CI = 2.45 to 10.97) were associated with increased risk of death. Conclusion: Screening older people for CKD may be of value, as their risk of short-term mortality, hospitalisation, and CVD is comparable with people routinely diagnosed. Larger studies with longer follow-up in more diverse and representative populations of older adults are needed to corroborate these findings.